Structure-Based Design, Docking, and Pharmacophore Mapping of Quinoline Derivatives as Potent Inhibitors of Plasmodium falciparum DHFR: A Computational Antimalarial Study - Yadav, Paresh Kapoor; Singh, Anuj Kumar; Somkuwar, Sushma; Khare, Rishabh; Manisha, Manisha; Kaur, Jaswinder; Kumar, Anil; Haque, Mohibul; Sharma, Ajay Kumar (Journal of Neonatal Surgery, 2025)
Background:Malaria, caused predominantly by Plasmodium falciparum, remains a major global health burden, with rising resistance to existing drugs such as pyrimethamine posing a significant challenge (World Health Organization [WHO], 2023). P. falciparum dihydrofolate reductase (PfDHFR) is a validated target for antimalarial therapy, but resistance mutations necessitate novel inhibitor designs. Quinoline derivatives offer a versatile scaffold with proven antimalarial potential and tunable chemical properties. Objective:To design, dock, and perform pharmacophore mapping of novel quinoline derivatives against PfDHFR, assessing their binding affinities, key molecular interactions, and predicted pharmacokinetic profiles to identify promising candidates for further development. Methods:Five quinoline derivatives—QD-1 (4-amino-7-chloroquinoline), QD-2 (2,6-dimethylquinoline), QD-3 (6-methoxyquinoline), QD-4 (quinoline-2-thiol), and QD-5 (quinoline-3-carboxylic acid)—were designed and optimized using density functional theory (DFT) calculations. Molecular docking was performed against PfDHFR (PDB ID: 1J3I) using AutoDock Vina, and 3D binding poses were visualized. ADMET properties were predicted via SwissADME, and pharmacophore mapping was conducted using Phase (Schrödinger). Results:QD-3 displayed the highest binding affinity (−10.2 kcal/mol), forming stable hydrogen bonds with key residues Ile14, Asp54, and Phe58, alongside strong hydrophobic contacts. QD-1 also demonstrated excellent binding (−9.8 kcal/mol) with favorable ADMET properties. Radar plots indicated that all derivatives were within optimal ranges for oral bioavailability. Pharmacophore mapping revealed that QD-3 and QD-1 matched all critical hydrogen bond donor, acceptor, and aromatic hydrophobic features of the generated model. Conclusion:Quinoline derivatives, particularly QD-3 and QD-1, exhibit strong PfDHFR inhibitory potential with favorable pharmacokinetic profiles, offering promising scaffolds for next-generation antimalarial development. These in-silico results warrant further in-vitro and in-vivo validation